Shaping the future of African American film : color-coded economics and the story behind the numbers - Ndounou, Monica White, 1976- (New Brunswick, N.J. : Rutgers University Press, 2013)
Through analysis of the production, funding, and content of thousands of films featuring African Americans in leading and supporting roles, Monica White Ndounou reveals the process of history and film development where race-based economics and the politics of distribution hamstring the making, the expression, and the creative freedom of films about, by, or for people of color.
Introduction: the color of Hollywood: black, white or green? -- Finding freedom on stage and screen. The plantation lives! -- Insurrection!: African American film's revolutionary potential through black theatre -- Black pathology sells: books and films -- Playing with fire: black women's literature/white box office -- A breaking the chains of history and genre -- It' not just business: color-coded economics and original films -- The paradox of branding, black star power, and box office politics -- Big business: hip hop gangsta films and black comedies -- Conclusion: the story behind the numbers.
Includes filmography.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: African Americans in the motion picture industry; Motion pictures -- Economic aspects -- United States; Motion picture industry -- United States -- Finance; African American motion picture producers and directors; African Americans in motion pictures; Noirs américains dans l'industrie cinématographique.; Producteurs et réalisateurs de cinéma noirs américains.; Noirs américains au cinéma.; Cinéma -- Industrie -- Aspect économique -- États-Unis.; Cinéma -- Industrie -- États-Unis -- Finances; PERFORMING ARTS -- Reference; African American motion picture producers and directors; African Americans in motion pictures; African Americans in the motion picture industry; Motion picture industry -- Finance; Motion pictures -- Economic aspects; United States; Filmwirtschaft; Schwarze; Schwarze; Film; Finanzierung; USA